The tumor suppressor RhoBTB1 controls Golgi integrity and breast cancer cell invasion through METTL7B. Issue 1 (December 2017) - McKinnon, Caroline; Mellor, Harry
Abstract Background RhoBTB1 and 2 are atypical members of the Rho GTPase family of signaling proteins. Unlike other Rho GTPases, RhoBTB1 and 2 undergo silencing or mutation in a wide range of epithelial cancers; however, little is known about the consequences of this loss of function. Methods We analyzed transcriptome data to identify transcriptional targets of RhoBTB2. We verified these using Q-PCR and then used gene silencing and cell imaging to determine the cellular function of these targets downstream of RhoBTB signaling. Results RhoBTB1 and 2 regulate the expression of the methyltransferases METTL7B and METTL7A, respectively. RhoBTB1 regulates the integrity of the Golgi complex through METTL7B. RhoBTB1 is required for expression of METTL7B and silencing of either protein leads to fragmentation of the Golgi. Loss of RhoBTB1 expression is linked to Golgi fragmentation in breast cancer cells. Restoration of normal RhoBTB1 expression rescues Golgi morphology and dramatically inhibits breast cancer cell invasion. Conclusion Loss of RhoBTB1 expression in breast cancer cells leads to Golgi fragmentation and hence loss of normal polarity.